Experimental and Computational Design of Nanostructured Materials for High Performance Supercapacitor Devices - Ali, Basant A. (AUC Knowledge Fountain, 2021)
Both energy conversion and storage technologies need to be developed hand-to-hand simultaneously to overcome the energy crises. To this end, supercapacitors (SCs) have the potential to be the energy storage platform due to their fast charging capability and long cycling stability. However, their low energy is the bottleneck towards their wide implementation compared to batteries. Also, current research is based on guess and check methods to modify electrode materials with limited properties prediction. In this thesis, density functional theory (DFT) has been employed as a tool to identify potential SC electrode materials. Then, the gained knowledge was used to develop sustainable solutions for the synthesis of SC electrode materials. The results showed that the use of basic electrolytes should ensure the highest capacitance performance of functionalized carbon-based electrodes, while neutral electrolytes should enable the highest potential window. Moreover, CNTs were shown to deliver the highest capacitance in comparison to various carbon allotropes. A symmetric device of CNTs revealed an energy density of 23.2 Wh/Kg at a power density of 475 W/Kg. Also, the results showed ion intercalation to enhance the quantum capacitance and stabilize the 1T phase of MoS2 and recommended the use of Cs+ intercalation for concentrated electrolyte supercapacitors and K+ intercalation for the diluted counterpart. Moreover, the 2H and 3R-MoS2 phases should be used only as positive electrodes, while the 1T-MoS2 can be employed as positive and negative electrodes. The 1T-MoS2 symmetric device revealed an energy density of 4.19 Wh/Kg at a power density of 225 W/Kg. Further, multi-metal sulfides showed superior performance, where the hybrid Ni-Mn-Co-S//graphene hydrogel device delivered an energy density of 49.55 Wh/Kg at a power density of 800 W/Kg. Interestingly, Li-Ni-Mn-Co hydroxides recycled from spent batteries showed a specific capacitance of 951 F/g at 1 A/g. Finally, a silk in-vivo chemically-modified electrode exhibited 5 folds of capacitance increase compared to the unmodified silk. Therefore, quantum capacitance and other DFT predictions are useful in screening electrode materials. Also, sulfide electrodes can exhibit very high capacitance performance either through intercalation or redox processes if combined in hybrid supercapacitor devices.